The Following Investigation of the Mapping on Emotion in “Tanpa Kemudian” Translated as "No Resolution” - Ririn Tasumbey; Dewa Made Agustawan (Asshika: Journal of English Language Teaching & Learning, 2024)
The present study focuses on the mapping of emotion in "Tanpa Kemenudian" translated into "No Resolution." The research is grounded in the theory of Natural Semantic Metalanguage (NSM), a concept that has been supported by Wierzbicka (1999) and Goddard (1997). The natural semantic metalanguage (NSM) is defined as a minilanguage believed to correspond to the common core of all languages. This hypothesis has emerged through comprehensive cross-linguistic inquiries that have spanned over three decades. The NSM system was developed primarily as a linguistic theory aimed at identifying the "language of thought" and the shared core of the lexicon and grammar of all natural languages. The present study explores the notion of emotion, delineating its association with positive and negative phenomena. The objective of the present study is to demonstrate that emotion mapping is imperative for effective translation. This ability will assist the translator in accurately conveying the intended message from the source language to the target language. The findings reveal that the data is distributed as follows: four data points are associated with favorable outcomes, while three data points are associated with unfavorable outcomes. Each lexicon is representative of its semantic features, as determined by the NSM approach.